2020
DOI: 10.1002/jssc.202000809
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of three iridoid glycosides of Rehmannia glutinosa in rat biological samples using a validated hydrophilic interaction–UHPLC–MS/MS method in pharmacokinetic and in vitro studies

Abstract: The purpose of this study was to develop a method for simultaneous analysis of aucubin, catalpol, and geniposide, which are representative iridoid glycoside constituents of Rehmannia glutinosa, in rat plasma, urine, and feces using hydrophilic interaction ultra high-performance liquid chromatography with tandem mass spectrometry. The three components were separated using 10 mmol/L aqueous ammonium formate containing 0.01% (v/v) formic acid and acetonitrile as a mobile phase by gradient elution at a flow rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Compound classification, diagnostic ions, and cleavage are shown in Figure 3. In this study, 22 triterpenes and their saponins were preliminarily identified [22][23][24]…”
Section: Hplc-q-tof-ms/msmentioning
confidence: 99%
“…Compound classification, diagnostic ions, and cleavage are shown in Figure 3. In this study, 22 triterpenes and their saponins were preliminarily identified [22][23][24]…”
Section: Hplc-q-tof-ms/msmentioning
confidence: 99%
“…It is the sum of the material basis for the efficacy of drugs against certain diseases [23]. In view of this characteristic of TCM, carrying out multi-component pharmacokinetic research by finding out those TCM ingredients that can be significantly utilized by the body through the changes in the content of medicinal substances after administration, is of great significance for revealing the material basis of the pharmacodynamics of TCM [24][25][26]. Simultaneously, the multi-component pharmacokinetic study of TCM can build a bridge between the chemical information and pharmacodynamic activity of TCM, infer the interaction between the ingredients, and provide a basis for the dosing regimen [27].…”
Section: Introductionmentioning
confidence: 99%
“…Geniposide metabolism involves methylation, glucosylation, decarboxylation, taurine conjugation, hydrolysis, demethylation, hydrogenation, hydroxylation, cysteine S-conjugation through dehydration, sulfate conjugation, and other related complex reactions. 20 , 21 Geniposide is mainly excreted in its original form through the kidneys. The excretion level accounts for a proportion of over 90% of the initial dosage after 10 h. 22
Figure 3 Schematic diagram of the metabolic effect of geniposide by β-glucosidase and esterase.
…”
Section: Introductionmentioning
confidence: 99%